Analyzing Hertzian contact stress developed in a double row spherical roller bearing and its effect on fatigue life. Issue 3 (11th April 2016) - Shah, Dhaval B.; Patel, Kaushik M.; Trivedi, Ruchik D.
Abstract : Purpose: The purpose of this paper is to describe a method permitting the creation of a realistic model of spherical roller bearing with the aim of determining contact stress and fatigue life based on dynamic loading conditions. The paper also aims to recognize the effect of tolerance values on contact stress and fatigue life. Motion and load transmission in spherical roller bearing occurs within the assembly by elliptical curved contacting surfaces. The stress produced by the transmitted load would be very high because of least contacting area between these surfaces. Design/methodology/approach: The paper describes a methodology to determine contact stress using analytically as well as finite element method for spherical roller bearing. The comparison for the both each approach for contact stress at different loading condition is carried out. Prediction of fatigue life based on dynamic loading conditions for bearing is also determined using finite element model. The effect on induced contact stress and fatigue life by varying tolerances on inner race dimensions have been found out. Findings: The paper suggests that the maximum stress produces at the start or end of the contacting arc under static loading condition in spherical roller bearing. The analytical and finite element approach is in good agreement. The fatigue life prediction is useful for selecting loading conditions for various applications of double row spherical roller bearing. Tolerance level at inner ring raceway radius is kept high because of manufacturing constrain of complex curvature geometric shape. Research limitations/implications: The present approach does not consider dynamic loading conditions for contact stress analysis. Therefore, researchers are encouraged to analyze the effect of wear, lubrication and other tribological aspects on bearing life. Originality/value: The paper includes determination of contact stress and prediction of fatigue life for spherical roller bearing using analytical as well as finite element approach. The tolerance values at inner race are identified as per manufacturing constraint based on contact stress and fatigue life.